Genotyping of Rotavirus by Using RT-PCR Methods - Nirwati, Hera; Wibawa, Tri; Aman, Abu Tholib; Soenarto, Yati (Indonesian Journal of Biotechnology, 2013)
There is a great diversity of rotavirus genotypes circulating worldwide, with dominant genotypes changing from year to year. Rotavirus genotyping was performed by using reverse transcription PCR with type-specifi c-primers. Since rotavirus is a RNA virus that has high mutation rate, there was a possibility of technical diffi culty in genotyping due to mutation in the primer binding sites. During Indonesian rotavirus surveillance study 2006-2009, it was reported that 17% of samples subjected for G type and 21% of samplessubjected for P type were untypeable. The objective of this study was to identify genotypes of the samples that were untypeable previously using RT-PCR based on the method described by Das et al. (1994) and Gentsch et al. (1992). There were 30 samples subjected to G type and 61 samples subjected to P type to be re-typed using method described by Gouvea et al. (1990) and Simmond et al. (2008) for G and P typing, respectively. By using another set of primer, the genotype of all samples was identifi ed. This study highlights the importance of a constant reconsideration of primer sequences employed for the molecular typing of rotaviruses.Key words: rotavirus, G typing, P typing